Solitary vitreous cysts: a series of case reports - A.B. Galimova; I.V. Baranchikova; G.I. Garipova; I.R. Karachurina; R.Yu. Ziyazetdinova (РМЖ "Клиническая офтальмология")
A.B. Galimova1, I.V. Baranchikova1, G.I. Garipova1, I.R. Karachurina1, R.Yu. Ziyazetdinova2 1Russian Center for Eye and Plastic Surgery, Bashkir State Medical University, Ufa,   Russian Federation 2Bashkir State Medical University, Ufa, Russian Federation Aim: to present a series of case reports of vitreous cysts and to discuss the diagnostic and management strategies employed in each case. Patients and Methods: a total of five patients with solitary vitreous cysts associated with various degenerative eye diseases were examined. All patients underwent a standard ocular examination and enzyme immunoassay to detect antibodies against Toxoplasma, Taenia solium, and Echinococcus. The followup period spanned a range of six to 18 months. Results: two patients exhibited unilateral vitreous cysts in association with pigmentary retinal degeneration. Published data indicate that this combination is the most prevalent. Two patients exhibited a vitreous cyst concomitant with degenerative myopia, and in one case, a rhegmatogenous retinal detachment was identified in the eye with the cyst. The potential etiology of these cysts is the migration of the retinal pigment epithelium into the vitreous, particularly during the formation of retinal tears. In one case, bilateral vitreous cysts were identified in conjunction with agerelated macular degeneration. To the best of our knowledge, this represents the inaugural description of this association. Throughout the observation period, the dimensions and location of the cysts remained consistent, and no additional discomfort was observed. Accordingly, we proceeded with the follow-up. Conclusion: in the majority of cases, vitreous cysts are benign and do not necessitate intervention. However, in instances where a cyst is situated in close proximity to the visual axis, it can potentially lead to visual impairment. In such cases, argon or Nd:YAG laser cystotomy or cyst removal via posterior pars plana vitrectomy may be indicated. It is imperative to differentiate vitreous cysts from other conditions that may present with similar symptoms, such as ocular toxoplasmosis, cysticercosis, echinococcosis, and pigmentary tumors. Keywords: cyst, vitreous body, pigmentary retinal degeneration, toxoplasmosis, cysticercosis, echinococcosis. For citation: Galimova A.B., Baranchikova I.V., Garipova G.I., Karachurina I.R., Ziyazetdinova R.Yu. Solitary vitreous cysts: a series of case reports. Russian Journal of Clinical Ophthalmology. 2024;24(3):144–150 (in Russ.). DOI: 10.32364/2311-7729-2024-24-3-9.